Dissociative Amnesia – A Challenge to Therapy - Angelica Staniloiu; Hans J. Markowitsch (International Journal of Psychotherapy Practice and Research, 2018)
The psychiatric disease of dissociative amnesia is described and illustrated with case reports. It is emphasized that dissociative amnesia has a stress or trauma-related etiology and that affected individuals, contrary to the still dominant clinical belief, are frequently more severely and enduringly affected. That means, most of them show severe retrograde amnesia for their biography, usually accompanied by changes in their personality and sometimes also by alterations in other cognitive and emotive domains. As many patients show the phenomenon of “la belle indifference”, their motivation for therapy or treatment of their amnesia is reduced. Patients also seem to a high degree to possess immature, unstable personality features. Nevertheless, a number of quite divergent, though largely not evidence-based, therapeutic approaches exist and are described. They are divided into (a) psychopharmacological and somatic treatments, (b) psychotherapeutic interventions, and (c) neuropsychological rehabilitation. Furthermore, detailed treatment strategies are provided.
Keywords: Dissociative Amnesia